Using Diastolic Blood Pressure to Diagnose Acute Stroke in Isolated Acute Vestibular Syndrome. (27th September 2016) - Matsumoto, Shoiku; Kishikawa, Masanobu; Okuyama, Tosiro; Yoshino, Shinichiro; Hirakawa, Katsuyuki; Nagano, Sukehisa; Yoshimura, Takeo
Abstract : Background: Although diagnosis of isolated acute vestibular syndrome (AVS) via physical examination has been reported, a great deal of experience is needed to interpret the results. Patients with AVS often cannot participate in a physical examination, and not every emergency department (ED) is equipped with a magnetic resonance imaging machine. Therefore, in isolated AVS, clinical factors other than those used by general physicians and/or residents are required to identify strokes in these patients. The aim of this study was to determine those clinical factors useful in differentiating stroke patients from isolated AVS patients in the ED setting. Methods: We examined the records of 116 consecutive patients who presented to the ED between May 2010 and April 2013 with AVS (acute vertigo or dizziness, nystagmus, nausea/vomiting, head‐motion intolerance, unsteady gait) and without auditory symptoms, head and/or neck pain, or neurological findings. Patients underwent diagnostic neuroimaging. Clinical characteristics and vital signs measured in the ambulance were assessed. Multivariate logistic regression analysis was performed to evaluate the associations of systolic blood pressure (SBP) ≥150 mmHg, diastolic blood pressure (DBP) ≥85 mmHg, heart rate, age ≥60 years, and dyslipidemia with stroke. Results: Stroke was diagnosed in eight of the 116 (6.9%) patients with isolated AVS. DBP ≥85 mmHg (odds ratio 29.0; 95% confidence interval 3.38–249) was the only significant and independent factor associated with stroke among patients with isolated AVS. Conclusion: This study identified DBP ≥85 mmHg to be a simple and useful clinical factor differentiating stroke from non‐stroke isolated AVS.